Genome‐Wide Association Mapping of Seedling Net Form Net Blotch Resistance in an Ethiopian and Eritrean Barley Collection. Issue 4 (1st July 2019) - Adhikari, Anil; Steffenson, Brian J.; Smith, Madeleine J.; Dill‐Macky, Ruth
ABSTRACT: The net form of net blotch, caused by Pyrenophora teres f. teres ( Ptt ), is an economically important disease of barley ( Hordeum vulgare L.) that is best managed by breeding for resistance. Previous linkage mapping and genome‐wide association studies (GWAS) have identified many resistance quantitative trait loci (QTL) in barley. Here we report eight novel resistance QTL identified in a unique collection of barley landraces from Ethiopia and Eritrea (EEBC) using a GWAS approach. Lines from the EEBC were genotyped with the Illumina barley iSelect chip and phenotyped with four Ptt isolates. A GWAS was conducted using the efficient mixed model association (EMMA) method with principal components and kinship to control false positives. Using a significance threshold of false discovery rate (FDR) of 0.05, two marker–trait associations (MTAs) were found on chromosomes 6H and 5H, respectively. Since this is a stringent method, markers in the lower 0.1 percentile of the p value distribution were also considered significant, identifying 20 unique MTAs. The 20 MTAs corresponded to 15 unique genomic loci, based on analysis of local linkage disequilibrium. Of the 15 QTL identified, one was identified in chromosome 1H, six in 2H, three each in 3H and 5H, and two in 6H. Eight of these QTL appear to be novel and thus could be of value to barley breeding programs to introgress novel net blotch resistance.